Peran Guru dalam Meningkatkan Motivasi Belajar Al-Qur'an Anak di Saung Qur'an Husnayain Jakarta Barat - Yokha Latief Ramadhan; Nayla Fayza Chairia (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2024)
This study aims to analyze the role of teachers in fostering children's enthusiasm for reciting the Qur'an at Saung Qur'an Husnayain. This research employed a qualitative approach involving 10 informants consisting of teachers, students, and parents. Data were collected through observation, semi-structured interviews, and documentation studies. The data were analyzed using the interactive model of data analysis, including data reduction, data display, and conclusion drawing. The findings reveal that teachers play multiple roles as educators, mentors, motivators, and parental figures in supporting children's Qur'anic learning. The study identified three main strategies used by teachers to enhance children's enthusiasm: (1) building emotional closeness with students, (2) applying interpersonal communication during the learning process, and (3) integrating enjoyable learning activities such as coloring and educational games. These strategies contributed to increased student participation, improved learning motivation, and greater consistency in attending Qur'an recitation sessions. In addition, a supportive learning environment, emotional encouragement, and attention to children's psychological needs were found to be important factors influencing the effectiveness of teacher interventions. Therefore, teachers play a crucial role in developing children's interest and sustained enthusiasm for learning and reciting the Qur'an from an early age.